Synthesis and Characterization of Cinnamon Loaded BSA Microparticles with Antidiabetic Properties - Wanniarachchi, Binuki; Sathsarani, H.M.W.K.; Jayawardena, Bimali M.; Dewangani, H.G.N. (Biology, Medicine, & Natural Product Chemistry, 2023)
Conventional medicine that is being used to treat diabetes exert adverse side effects and therefore scientists have focused on natural hypoglycemic agents. “Sri Wijaya” (CCSW) is an accession of Cinnamomum zeylanicum, which shows higher hypoglycemic activity. Pressured water extract of its dried quills can be used as an antidiabetic nutraceutical. Higher stability, ease of storage and transportation, make powder form nutraceuticals more preferred. The objective of this study was to develop cinnamon encapsulated microparticles as a powder form nutraceutical with higher hypoglycemic activity. Four different products were synthesized. Two of them were synthesized using bovine serum albumin (BSA) (8.8 % (w/v), pH=5) in the presence of citric acid and ascorbic acid as cross-linking agents separately. The other products were synthesized using BSA (20 mg/ mL, pH=9) in the presence of same cross-linking agents. Antidiabetic activity of the products was determined using alpha-amylase and alpha glucosidase inhibition assays and compared with that of crude cinnamon extract and positive control acarbose. Since the product synthesized using BSA (20 mg/ mL, pH=9) and citric acid showed the highest alpha amylase inhibition activity, solubility, cinnamon loading percentage and cinnamon entrapment efficiency those conditions were concluded as the optimum conditions required to synthesize microparticles with higher hypoglycemic activity. Particle size, polydispersity index, and zeta potential of that product were 1.281 ± (0.004) µm, 0.460 ± (0.018) and -1.09 ± (0.03) mV respectively. According to the SEM image, microparticles have a spherical morphology. The UV-visible spectrum and the FT-IR spectrum confirm the entrapment of cinnamon compounds.